Molecular mechanisms and therapeutic potential of lithium in Alzheimer’s disease: repurposing an old class of drugs - Shen, Yanxin; Zhao, Meng; Zhao, Panpan; Meng, Lingjie; Zhang, Yan; Zhang, Guimei; Taishi, Yezi; Sun, Li (Frontiers in Pharmacology, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and memory loss. Despite advances in understanding the pathophysiological mechanisms of AD, effective treatments remain scarce. Lithium salts, recognized as mood stabilizers in bipolar disorder, have been extensively studied for their neuroprotective effects. Several studies indicate that lithium may be a disease-modifying agent in the treatment of AD. Lithium’s neuroprotective properties in AD by acting on multiple neuropathological targets, such as reducing amyloid deposition and tau phosphorylation, enhancing autophagy, neurogenesis, and synaptic plasticity, regulating cholinergic and glucose metabolism, inhibiting neuroinflammation, oxidative stress, and apoptosis, while preserving mitochondrial function. Clinical trials have demonstrated that lithium therapy can improve cognitive function in patients with AD. In particular, meta-analyses have shown that lithium may be a more effective and safer treatment than the recently FDA-approved aducanumab for improving cognitive function in patients with AD. The affordability and therapeutic efficacy of lithium have prompted a reassessment of its use. However, the use of lithium may lead to potential side effects and safety issues, which may limit its clinical application. Currently, several new lithium formulations are undergoing clinical trials to improve safety and efficacy. This review focuses on lithium’s mechanism of action in treating AD, highlighting the latest advances in preclinical studies and clinical trials. It also explores the side effects of lithium therapy and coping strategies, offering a potential therapeutic strategy for patients with AD.